1997
DOI: 10.1095/biolreprod57.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-Stimulating Hormone Stimulates Circulating Gonadotropin Surge-Attenuating/Inhibiting Factor Bioactivity in Cows1

Abstract: This study aimed to determine whether superovulation in cattle stimulates gonadotropin surge-attenuating/inhibiting factor (GnSAF/IF) bioactivity, as it does in humans. Blood samples were collected from cows (n = 7 per treatment) at -4, 8, 20, 32, 44, 56, and 68 h after injections of saline, eCG, or FSH. Equal volumes of plasma at each treatment and time point were pooled, and GnSAF/IF and inhibin bioactivities were measured using an established rat pituitary cell culture bioassay. Plasma from saline- and eCG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This is consistent with our previous data (Gosselin et al 2000) demonstrating that neither estradiol nor progesterone was correlated with LH pulsatility during superstimulation, a finding that was also confirmed by others (Takagi et al 2001). Other factors including (but not limited to) inhibin or the gonadotropin-surge inhibiting factor (Fowler and Price 1997), may be involved in the suppression of LH pulsatility during superstimulation. In the CIDR-7d group, the number of unovulated follicles increased and ovulation rate and embryo production decreased in animals with lower progesterone concentrations at the start of superstimulatory treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our previous data (Gosselin et al 2000) demonstrating that neither estradiol nor progesterone was correlated with LH pulsatility during superstimulation, a finding that was also confirmed by others (Takagi et al 2001). Other factors including (but not limited to) inhibin or the gonadotropin-surge inhibiting factor (Fowler and Price 1997), may be involved in the suppression of LH pulsatility during superstimulation. In the CIDR-7d group, the number of unovulated follicles increased and ovulation rate and embryo production decreased in animals with lower progesterone concentrations at the start of superstimulatory treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A line of evidence dating back to the late 1970s supports the existence of such a factor in humans as well as in other species (Ferraretti et al, 1983;Geiger et al, 1980;Koppenaal et al, 1992;Messinis et al, 1985Messinis et al, , 1986Templeton, 1989, 1991;Schenken and Hodgen, 1983;Sopelak and Hodgen, 1984). It has been suggested that FSH is the main hormone that stimulates the production of GnSAF (Fowler and Price, 1997;Messinis et al, , 1993Messinis et al, , 1994a. From a physiological point of view, it has been postulated that GnSAF, by antagonizing the stimulating effect of oestradiol on the pituitary, controls the amplitude of the LH surge and the coordination of the LH signal with follicular development and steroidogenesis in women and other mammals (Fowler et al, 2001(Fowler et al, , 2003Messinis et al, 1985Messinis et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Gonadotrophin surge‐inhibiting factor (GnSIF, also called gonadotrophin surge‐attenuating factor, GnSAF) has been known for over two decades, yet its molecular structure has still not been completely characterized. GnSIF/AF is an ovarian product, originating from the granulosa cells (Fowler et al, 2002), and its production is stimulated by follicle stimulating hormone (FSH) (Messinis et al, 1991; Fowler and Price, 1997). GnSIF/AF, in turn, inhibits the gonadotrophin‐releasing hormone (GnRH)‐induced pituitary luteinizing hormone (LH) secretion (Messinis and Templeton, 1991; Fowler et al, 2003) and antagonises the self‐priming effect of GnRH, both in vivo (Messinis and Templeton, 1991) and in vitro (Koppenaal et al, 1992; Fowler et al, 1994; Byrne et al, 1996; de Koning et al, 2001).…”
Section: Introductionmentioning
confidence: 99%